Optimization of the Batik Creative Industry through Technological Innovation to Improve Product Quality, Quantity, and Cost Efficiency in the City of Probolinggo - Augustinah, Fedianty; Tampubolon, Liosten Rianna Roosida Ully; Suyanto; Simanjuntak, Nensy Megawati; Sutejo, Bambang (Pascasarjana Universitas Mataram, 2025)
The Higher Education Community Service Program for Regions (PM-UPUD) aims to optimize the batik creative industry in Probolinggo City through the application of technological innovations. Target partners include Batik Wahyulatri and Poerwa Batik, which face problems such as limited raw material planning, motif and coloring quality, drying technology, and digital marketing strategies. The implementation methods include socialization, training, technology application, mentoring, and evaluation. The technologies applied include Wastewater Treatment Plant (IPAL), infrared dry room machines, Material Requirement Planning (MRP), synthetic coloring techniques, and digital marketing. The program results showed significant improvements: 40% in production capacity, 30% in dyeing quality, 20% in sales turnover for partner 1 and 25% for partner 2, as well as 30% and 36% in profits, respectively. This program supports ASTA CITA number 3 and SDGs number 8 on decent work and sustainable economic growth.